Evaluation of thiol/disulfide homeostasis in patients with gestational diabetes mellitus. (1st November 2020) - Cakina, Suat; Aydın, Buket; Beyazit, Fatma
Abstract: This study aimed to study the dynamic thiol/disulfide homeostasis in pregnant women with gestational diabetes mellitus (GDM). Forty-five pregnant women with GDM and 45 age-matched healthy pregnancies were included in this study. Thiol/disulfide homeostasis was measured using a commercial kit (Rel Assay Diagnostics). The patients with GDM had significantly higher disulfide concentrations than healthy pregnant patients ( p = .001). Besides, the GDM group had significantly higher disulfide/total thiol, disüplhide/native thiol, and native thiol/total thiol ratio than healthy pregnant patients ( p = .001, p = .001 and p = .001, respectively). The significantly higher concentrations of disulfide, disulfide/total thiol, disüplhide/native thiol, and native thiol/total thiol ratio in women with GDM could be considered as the increased oxidative stress.